2019
DOI: 10.1037/ort0000310
|View full text |Cite
|
Sign up to set email alerts
|

Culturally adapted transdiagnostic CBT for SSRI resistant Turkish adolescents: A pilot study.

Abstract: The most common mental health problems among adolescents are anxiety and mood disorders. While disorder-specific cognitive behavior therapy (CBT) is effective for each of these conditions, the comorbidity between anxiety and mood disorders indicates a need for the development of evidence-based transdiagnostic treatments. To examine the efficacy of culturally adapted transdiagnostic CBT (CA-CBT) in reducing symptoms of anxiety and depression in treatment-resistant Turkish adolescents, 13 adolescent participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Although there is a nearly medium effect size for anxiousdepressive distress as revealed by the HSCL (d = .40) and a large effect size for trauma symptoms (d = 1.17) in terms of change in symptom severity, the decrease in the treatment group was identical from baseline to postassessment. Previous studies with CA-CBT found statistically significant decreases in the participants' anxiety and depression symptoms (Acarturk et al, 2019;Hinton et al, 2004Hinton et al, , 2005Hinton et al, , 2009Hinton et al, , 2011 and somatic symptoms Jalal et al, 2017Jalal et al, , 2018 as well as increased psychological well-being (Jalal et al, 2017(Jalal et al, , 2018. Findings of this study are compatible with the literature, and small change in anxiety and depression scores from baseline to postassessment in treatment group who received CA-CBT may be related to the small sample size of the study, as encountered in similar situations in other studies (Dawson et al, 2016).…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Although there is a nearly medium effect size for anxiousdepressive distress as revealed by the HSCL (d = .40) and a large effect size for trauma symptoms (d = 1.17) in terms of change in symptom severity, the decrease in the treatment group was identical from baseline to postassessment. Previous studies with CA-CBT found statistically significant decreases in the participants' anxiety and depression symptoms (Acarturk et al, 2019;Hinton et al, 2004Hinton et al, , 2005Hinton et al, , 2009Hinton et al, , 2011 and somatic symptoms Jalal et al, 2017Jalal et al, , 2018 as well as increased psychological well-being (Jalal et al, 2017(Jalal et al, , 2018. Findings of this study are compatible with the literature, and small change in anxiety and depression scores from baseline to postassessment in treatment group who received CA-CBT may be related to the small sample size of the study, as encountered in similar situations in other studies (Dawson et al, 2016).…”
supporting
confidence: 86%
“…Though studies indicate higher prevalence rates of mental health problems among Syrian refugees (Acarturk et al, 2019;Alpak et al, 2015), a recent study reported a considerable treatment gap for PTSD, depression, and anxiety among Syrian refuges (Fuhr et al, 2019). Mental health treatment costs, stigmatization, and the belief that mental health symptoms may get better in time seemed to be the main barriers to seeking treatment among Syrian refugees in Turkey (Fuhr et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive behavioral therapy (CBT) has been consistently identified as an effective approach for treating anxiety (DiMauro et al., 2013; Sigurvinsdóttir et al., 2020) and depression (Hvenegaard et al., 2019; Mahmoodi et al., 2020) symptomatology. However, many international researchers and practitioners characterize CBT as being too Westernized to be broadly applicable to culturally diverse populations (Acarturk et al., 2019; Naeem et al., 2019; Yoshinaga et al., 2013) and may fail to meet the needs of persons from diverse backgrounds (Beck & Naz, 2019; Graham et al., 2013; Naeem, 2019). Moreover, given the disparity between the values of Western and Eastern cultures (e.g., individualism vs. collectivism, emotive vs. cognitive), some researchers have argued that using non‐culturally adapted psychotherapies across cultural groups may result in cultural identity erasure for minority groups (Laungani, 2004; Lorelle et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…CA multiplex CBT has been shown to be effective in randomized controlled trials with a waitlist control for traumatized Southeast Asian refugee patients from Cambodia and Vietnam, showing medium to large effect sizes in all studies on the posttraumatic stress disorder (PTSD) measure, with a between-group Cohen’s d of .45 or higher for the PTSD measure in all studies (Hinton, Hofmann, Pollack, & Otto, 2009; Hinton et al, 2004, 2005; Otto et al, 2003). CA multiplex CBT has also been shown to be effective with other groups, namely, with Latino patients, Farsi speakers, an Egyptian group, a South African tribal group (the Sepedi), and Turkish adolescents (Acarturk et al, 2018; Hinton, Hofmann, et al, 2009; Hinton, Hofmann, Rivera, Otto, & Pollack, 2011; Jalal, Kruger, & Hinton, 2018; Jalal, Samir, & Hinton, 2017; Kananian, Ayoughi, Farugie, Hinton, & Stangier, 2017; Shaw, Ward, Pillai, & Hinton, 2018).…”
mentioning
confidence: 99%